PEMBERLAKUAN UMK (UPAH MINIMUM KABUPATEN/KOTA) TERHADAP KESEJAHTERAAN PEKERJA/BURUH - Michele Agustine; I Gusti Ketut Ariawan (Kertha Negara : Journal Ilmu Hukum, 2013)
Wages play an important role and it is typical that is a industrial relation. Thegovernment has participated in addressing the issue of wages through various policiesas outlined in the legislation, one of which is the minimum wage. In a private company,has set minimum wages Regencies / Cities (UMK) has been established by thegovernment for the workers / laborers. Therefore, this paper will describe theapplication of minimum wages Regencies / Cities on the welfare of workers / laborers.